Setting the agenda for diabetes research in the state of Qatar - Amit Mishra; Suresh Babu Kokku; Ioanna Skaroni; Kholoud Ateeq Al Motawaa; Mohammed Al‐Thani; Nicholas Wareham; Abdul Badi Abou‐Samra; Shahrad Taheri (Wiley, 2023)
Abstract Background The burden of non‐communicable diseases, including diabetes, is high in the Middle East and North Africa (MENA) region. Qatar (a MENA country) has a high prevalence of diabetes (16.7%). Over the past 20 years, Qatar has made significant investment to establish a biomedical research infrastructure. This article documents the processes adopted for the development of a national diabetes research agenda for Qatar. Methods To develop the diabetes research agenda, a three‐step process was adopted. First, a bibliometric analysis of diabetes‐related research publications was conducted to understand current research and funding patterns. Second, through in‐depth interviews and a national consultative workshop, the challenges associated with diabetes research and their potential solutions were documented. Third, an expert team assimilated the recommendations to finalise the diabetes research agenda for the State of Qatar. Results A steadily increasing number of diabetes research publications and collaboration with researchers from 48 different countries was noted. Aetiological research (49%), mainly from cohort studies, dominated research publications. The national diabetes research agenda prioritised five research areas focused on diabetes prevention, early detection, reversal, treatment development and evaluation and system research for improved outcomes. Under each area, a set of research questions were identified to guide the research community to align their research interests with high‐priority research in diabetes. Conclusion The national research agenda development process has uncovered some important knowledge gaps and outlined the most impactful areas for diabetes research. Achievement of the objectives of the research agenda requires enhanced collaboration among the research community, sustained research funding and enabling a robust regulatory framework.